Crystallization and preliminary structural studies of champedak galactose-binding lectin - Gabrielsen, M.; Riboldi-Tunnicliffe, A.; Abdul-Rahman, P.S.; Mohamed, E.; Ibrahim, W.I.W.; Hashim, Onn Haji; Isaacs, N.W.; Cogdell, R.J. (2009)
Galactose-binding lectin from champedak (Artocarpus integer) consists of two chains: alpha and beta (133 and 21 amino acids, respectively). It has been shown to recognize and bind to carbohydrates involved in IgA and C1 inhibitor molecules. The protein was purified and crystallized at 293 K. Crystals were observed in two space groups, P2(1) and P2(1)2(1)2, and diffracted to 1.65 and 2.6 angstrom, respectively.